Numerical simulation of residual stresses induced by weld repair in a stainless steel pipe considering the influence of an initial fabrication weld - Salerno, Gervasio; Bennett, Chris; Sun, Wei; Becker, Adib A. (2016)
This work presents the application of a finite element (FE) model developed to simulate the repair process in the case of components with a pre-existing stress state. The approach is tested in the case of a repair of a laser beam weld in a stainless steel pipe with the region of repair located in the heat affected zone of the original weld. The area of the repair is removed and refilled testing different approaches in terms of the number, and direction of the repair passes. The comparison between the refilling procedures is presented with the aim of evaluating the effects on the final residual stress distribution.